Effects of graded levels of vitamin C supplemented feed of layers on serum concentrations of vitamin A and vitamin C - Sanda, ME; Suleiman, A (Asian Journal of Medical and Biological Research, 2015)
The study was conducted to determine the effects of layers? diets containing 0, 100, 150 and 200 mg/kg vitamin C on vitamin A and C concentrations in serum of layers. A total of 80 Isa brown layers (28 weeks of age) were used in this study. There were a control and three treatment groups each containing 20 hens. The experimental period lasted 8 weeks. Serum vitamin A and vitamin C concentrations were determined twice at 32 and 36 weeks of age. Serum vitamin A and serum vitamin C concentrations increased as vitamin C supplementation increased in the diet. During the study, serum concentration of vitamin C was increased significantly (P<0.05) by the addition of 150 and 250 mg/kg vitamin C and serum concentration of vitamin A was increased significantly (P<0.01) in all treatment groups in increasing order as vitamin C supplementation increases in the diet. It has been concluded that vitamin C protected vitamin A against oxidation and increased serum vitamin A levels in parallel with increased serum vitamin C. Asian J. Med. Biol. Res. June 2015, 1(2): 158-162